(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Modern educational systems increasingly emphasise learner-centred approaches that consider learners’ cognitive, perceptual, and psychological characteristics. In contemporary education, creating a motivational learning environment is essential for maintaining learners’ engagement, improving academic performance, and supporting individual development. This article explores the role of neuro-adaptive modular educational technology in developing a motivational learning environment for learners. Using a qualitative research approach based on literature review and analysis of educational practices, the study examines how neuro-adaptive mechanisms and modular instruction contribute to learning motivation, cognitive engagement, and educational effectiveness. The findings suggest that adaptive and personalised learning environments enhance learner participation, reduce cognitive overload, and address individual learning needs more effectively. The article concludes that neuro-adaptive modular educational technology significantly contributes to improving the quality, flexibility, and efficiency of modern education.